Avatar, the last airbender. Book 3. Fire [videorecording (DVD)] - DiMartino, Michael Dante; Konietzko, Bryan (Paramount, 2015)
"Aang faces new challenges as he and his friends infiltrate the Fire Nation in order to find and defeat Firelord Ozai. They soon discover that Ozai intends to use the massive power of Sozin's Comet to conquer the Four Nations."--Container.